Safety and immunogenicity of meningococcal A and C polysaccharide conjugate vaccine in adults. - Anderson, E L (1994)
A meningococcal vaccine containing group A and C polysaccharides conjugated to CRM197 was evaluated in 50 adults. Vaccinees were entered into one of five groups: 30 adults received a single dose of either 22, 11, or 5.5 micrograms of the conjugated A-C vaccine; 10 received an approved meningococcal vaccine; and 10 received saline injections. Local and systemic reactions to vaccines were recorded, and immune responses were determined. The experimental meningococcal vaccine was well tolerated, with the most frequent reaction being pain at the injection site. Both A and C polysaccharide components of the experimental vaccine were highly immunogenic, and total antibody concentrations 1 month postvaccination were not significantly different from the mean antibody concentrations among adults given the approved meningococcal vaccine. In addition, significant rises in immunoglobulin G, A, and M antibodies to both A and C polysaccharides occurred. Antibody concentrations measured at 6 and 12 months postvaccination had declined but remained significantly higher than prevaccination concentrations. Postvaccination meningococcal group C functional antibody activity increased more than 600-fold for both the polysaccharide and the conjugate vaccines. Further studies of this conjugated meningococcal vaccine are indicated for young children and infants.